Sweat rates and fluid intakes of Olympic-standard divers in training - Ranchordas, M; Rogerson, D. (International Journal of Sport Nutrition and Exercise Metabolism, 2013)
Very little data on fluid balance in elite divers exist, so the purpose of this study was to investigate fluid intake and sweat rates in Olympic-standard divers during a training session. Thirteen divers (6 men, 7 women) who had either competed at an Olympic Games or had qualified for the 2008 Beijing Olympics participated in this study. Sweat rates were measured by changes in body mass and corrected for fluid ingestion and urine output. This equation does not take into account substrate oxidation and respiratory losses thus, the limitations of this method are acknowledged. The training session lasted 145 min, where 65 min was conducted on dry land (air temp. 21.2°C) and 80 min in the pool (air temp. 35.4°C, water temp. 26.1°C). Mean urine osmolality pretraining was 436 ± 174 mOsmol/kg. Total mean sweat volume loss during the training session was 0.52 ± 0.08 L and 0.60 ± 0.11 L of fluid was ingested. Sweat rates in the pool were higher than in dry land (0.24 ± 0.07 vs. 0.18 ± 0.04 L/h, p < .001), but there were no differences in either sweat rates or fluid consumed between men and women divers. Total mean sweat rates for the training session was 0.22 ± 0.3 L/h. Sweat rates in Olympic-standard divers are similar to those reported for other aquatic athletes such as swimmers and water polo players. The divers in this study remained hydrated and some even ingested more fluid than required.